Case Report: A novel compound heterozygosity of the EVC2 gene identified in a Chinese pedigree with congenital heart defect - Xu, Xiayuan; Gao, Chengcheng; Jin, Keqin; Zhang, Liping; Yang, Yanfen; Zhang, Jun; Ye, Yun; Shen, Shuangshuang (Frontiers in Pediatrics, 2025)
BackgroundCongenital heart defects (CHDs) represent the leading cause of neonatal mortality among congenital abnormalities. Genetic factors, such as EVC2 gene mutations and other genetic alterations, constitute a major cause of CHD. Thus, determining the genetic etiology of fetal CHDs is crucial for optimizing pregnancy management and informing future reproductive decisions.Case presentationHere, we describe a male fetus with complex CHD who was diagnosed at 25 weeks of gestation, delivered at full term, and died prematurely within a month due to heart failure. The cardiac abnormalities observed included an atrial septal defect developing from a patent foramen ovale, mitral valve regurgitation, dilated right ventricle and left atrium, aortic stenosis, and aortic arch dysplasia. Novel compound heterozygosity of the EVC2 gene, including a non-sense mutation (p.W828Ter) and two cis missense mutations (p.E87G and p.S217C), was identified by prenatal trio-whole-exome sequencing of amniotic fluid, followed by validation using Sanger sequencing. This novel EVC2 genotype was supposed to potentially affect fetal cardiac development, given the variable clinical heterogeneity of the EVC2 mutation-associated phenotype. This case represents the first identification of the EVC2 p.E87G and p.S217C, and the isolated CHD without visible skeletal dysplasia is an important feature of our case.ConclusionsOur study expands the genotypic and phenotypic spectra of the EVC2 gene. We recommend including the EVC2 gene in preconception carrier screening and prenatal diagnosis for CHDs.